2018
DOI: 10.1186/s13075-018-1728-3
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and adverse events of biological treatment in adult patients with juvenile idiopathic arthritis: results from BIOBADASER

Abstract: BackgroundBiologic therapy has changed the prognosis of patients with juvenile idiopathic arthritis (JIA). The aim of this study was to examine the pattern of use, drug survival, and adverse events of biologics in patients with JIA during the period from diagnosis to adulthood.MethodsAll patients included in BIOBADASER (Spanish Registry for Adverse Events of Biological Therapy in Rheumatic Diseases), a multicenter prospective registry, diagnosed with JIA between 2000 and 2015 were analyzed. Proportions, means,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(36 reference statements)
1
3
0
Order By: Relevance
“…Nevertheless, even in the subgroup of this cohort that had the disease onset after the year 2000, 41.6% started the bDMARD later than 5 years of disease onset. This is in line with other registries like Biker and Biobadaser, which showed that in 2000, only around 25% of patients received the first biologic at a pediatric age, with this percentage increasing linearly until reaching 65% in 2015 [8,26].…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, even in the subgroup of this cohort that had the disease onset after the year 2000, 41.6% started the bDMARD later than 5 years of disease onset. This is in line with other registries like Biker and Biobadaser, which showed that in 2000, only around 25% of patients received the first biologic at a pediatric age, with this percentage increasing linearly until reaching 65% in 2015 [8,26].…”
Section: Discussionsupporting
confidence: 91%
“…Recent German pJIA therapy algorithms include tocilizumab in the first-line use of biological agents [9], as do the Childhood Arthritis and Rheumatology Research Alliance (CARRA) Consensus Treatment Plans [8]. The pathways of using biological agents in clinical practice are constantly changing [10,20] and vary considerably in different countries due to local regulations and availability of the biological agents [11,12,[20][21][22]. Since there is rather short experience of tocilizumab in the treatment of pJIA, only few register and observational reports have been published on the safety and efficacy of tocilizumab so far [11,12,16].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the hopeful results of this retrospective study, data from the ABC registry revealed that despite the high rates of good response to etanercept in psoriatic JIA patients, 5/6 patients who ceased treatment at 22 months flared at a median of 2 months ( Otten et al, 2011b ). Finally, longer retention of the first biologic, as well as increased frequency of treatment suspension due to remission was observed in patients aged less than 16 years at the initiation of biologic therapy, as per data from a Spanish biologic registry ( Bethencourt Baute et al, 2018 ).…”
Section: Various Predictor Biomarkers For Successful Withdrawal Of Bimentioning
confidence: 88%